The Development and Implementation of Modified Machine Guns of the UKM 2000 Family (Calibre: 7.62 mm) - Damian JAROSZ; Damian CICHY; Wojciech GOŁĄB; Karol WILK (Problemy Mechatroniki, 2019)
Zakłady Mechaniczne TARNÓW S.A. (ZMT, Tarnów, Poland), the manufacturer of the UKM 2000 family of 7.62 mm machine guns, has extensive experience producing and factory-repairing those guns, and collect the comments and observations of the weapon’s users. Taking them into consideration, ZMT has decided to modify the UKM 2000 family. The decision coincided with the stance of the MoD’s Armament Inspectorate, which suggested implementing such a modification, providing a detailed determination of its range (“Modification Guidelines”). First, the changes were introduced in the infantry version (UKM 2000P), then in the onboard version (UKM 2000C). The core aims of the modification were: increasing the weapon’s reliability and durability, improving the technology and ergonomics, and minimising the number of parts and groups that require individual fitting. Initially, the changes were supposed to encompass only a modest number of parts and groups; however, during the design works, the necessity to introduce deep modifications to the most important rifle elements, i.e. the bolt, the slide, the pin, the gas regulator and the feeding mechanism, appeared. During the research on the 7.62 mm modified UKM 2000P machine guns, properties such as the weapon’s operation in low temperatures, as well as its resistance to dynamic interaction with dust and sand, salt fog, and elevated humidity were investigated. ZMT placed the first batch of the machine guns under monitored operation, and the observations made during use so far clearly confirm the soundness and range of the changes introduced. It should be kept in mind, however, that it is not possible to develop a single, universal weapon configuration that would meet the needs of all users. Direct exchange of feedback between the User and the Manufacturer allows the structure to be optimised and guarantees development in the field in question.